Nutritional Properties, Phytochemicals and In Vitro Antioxidant Assessment of Two Wild Edible Fruits from Assam of North-East India - Anuck Islary; Jatin Sarmah; Sanjay Basumatary (Journal of Pharmacy and Nutrition Sciences, 2017)
The aim of present study was to ascertain the nutritional properties, phytochemical contents and in vitro antioxidant capacities of two wild edible fruits viz. Aporosa dioica (Roxb.) Muell.-Arg. and Ottelia alismoides (L.) Pers. found in Assam of North-East India. Nutritional properties, phytochemical screening, total phenolic content (TPC) and total flavonoid content (TFC) were investigated employing standard methods. Antioxidant properties were assessed following DPPH (1, 1-diphenyl-2-picrylhydrazyl), ABTS (2, 2´-Azinobis (3-ethylbenothiazoline-6-sulfonic acid) diammonium salt), H2O2 (Hydrogen peroxide) and FRAP (Ferric reducing antioxidant power) assays. The results obtained in this study were presented and discussed. A. dioica fruit extract exhibited lower IC50 (DPPH, ABTS and H2O2) values in contrast to O. alismoides fruit extract indicating stronger antioxidant capacity in A. dioica fruit. Higher FRAP value of 106.583 ± 5.204 ?M trolox equivalent (TE)/g dry extract (DE) was found in the methanol extract of A. dioica fruit compared to that of O. alismoides fruit (44.083 ± 7.637 ?M TE/g DE). The TPC found in the methanol extracts of A. dioica and O. alismoides fruits were 146.710 ± 2.807 mg gallic acid equivalents (GAE)/g DE and 93.860 ± 1.172 mg GAE/g DE, respectively, while the TFC was found to be 72.510 ± 8.833 mg quercetin equivalents (QE)/g DE in A. dioica fruit and 43.270 ± 5.361 mg QE/g DE in O. alismoides fruit. These fruits are good sources of nutrients and natural antioxidants and may find applications in formulation of various pharmaceutical drugs.